Faktor-Faktor yang Mempengaruhi Penyaluran Kredit BPR di Provinsi Bali - Maha Yoga, Gede Agus Dian; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
In the economic development of Rural Banks as financial institutions that is one source of financing for micro small and medium enterprises in extending credit is influenced by internal and external factors. The purpose of this study was to determine the effect of simultaneous or partial between Third Party Funds (TPF), Gross Regional Domestic Product (GRDP), Interest Rate (IR), and Non Performing Loan (NPL) to Rural Banks lending in the fourth quarter of Bali Province years 2000-2011, the analysis technique used in this study is multiple linear regression. Based on test results, simultaneously TDF, GRDP, IR, NPL significant effect on Rural Banks lending in the fourth quarter of Bali Province from 2000 to 2011. Partially TPF significant positive effect and GRDP had no significant effect, while IR variable significant negative effect and NPL no significant effect on Rural Banks lending in the fourth quarter of Bali Province 2000 – 2011.
Keywords: Dana Pihak Ketiga (DPK); Produk Domestik Regional Bruto (PDRB); Suku Bunga Kredit (SBK); Non Performing Loan (NPL); Penyaluran Kredit